COVID-19 and Immunosuppressive Therapy in Ocular Inflammatory Disease, a Telemedicine Survey. (19th May 2021) - Ebrahimiadib, Nazanin; Fadakar, Kaveh; Riazi-Esfahani, Hamid; Zarei, Mohammad; Maleki, Arash; Bojabadi, Leila; Ahmadi, Amin; Look-Why, Sydney; Foster, C Stephen
ABSTRACT: Purpose : Determine the risk of immunomodulatory therapy (IMT) for COVID-19 infection morbidity. Method : A telemedicine survey on patients of a referral uveitis clinic was performed. Signs of infection, habits, and hospitalizations during the 7 months of the COVID-19 pandemic prior to the study date were recorded. Suggestive findings in chest CT scan and/or positive RT-PCR were considered as confirmed COVID-19 infection while those with only suggestive symptoms were considered as suspected cases. Risk factors including sanitary measures and IMT were compared between patients with confirmed cases and patients without infection. Result : 694 patients were included. Eight patients were identified as confirmed cases and 22 patients as suspected cases of COVID-19 infection. Close contact with infected persons was the only significant risk factor for contracting COVID-19. Conclusion : Using IMT did not affect hospitalization and/or ICU admission and can thus be continued during the pandemic, provided that instructions for preventive measures are followed.